Are short sellers positive feedback traders? Evidence from the global financial crisis - Bohl, Martin T.; Klein, Arne C.; Siklos, Pierre L. (Journal of Financial Stability, 2013)
Short sellers are routinely blamed for destabilizing stock markets by exacerbating deviations from fundamental values. In response, regulators periodically impose short sale constraints aimed at preventing excessive stock market declines. One explanation is that policy makers regard short sellers as behaving like positive feedback traders. Relying on the theoretical model put forward by Sentana and Wadhwani (1992), which stresses the conditional nature of returns’ persistence, bans on selected financial stocks in six countries during the 2008/2009 global financial crisis are examined. These provide us with a setting to analyze the impact of short sale restrictions on feedback trading. Our findings suggest that, in the majority of markets examined, restrictions of this kind amplify positive feedback trading during periods of high volatility and, hence, contribute to stock market downturns. On balance then, short selling bans do not contribute to enhancing financial stability.